Performance of public administrations in the Covid era - EL MOUISSIA , Rim; BENABDELHADI , Abdelhay (Revue Internationale du Chercheur, 2022)
In an already strained economic context, the recent appearance of devastating crises that followed the worldwide spread of Covid 19, has created many challenges to all organizations, from public or private sector, hindering their ability to prosper and be efficient. Today more than ever, performance is at the heart of the attention of many organizations’ strategies and action plans. In 2011, the Moroccan government has launched multiple reforms aiming to modernize the public sector that led to the institution of the new organic law n°130-13 related to the finance law (LOF). This law placed performance as one of its main pillars through a shift from a logic of means to one set around results. It has also promoted the principals of good governance and reinforced the role of supervisory authorities to guarantee performance in the public sphere and ensure the cohesion of public policies. The functioning of public administrations went from a strictly legal and technical approach to one favoring managerial culture at the service of citizens. The concept of performance has greatly evolved through the evolution of management theories and with the occurrence of the pandemic, one can therefore ask how performance of public administrations is perceived and measured. In this context, this article aims to examine through a literary review around the concept of performance, the impact of the Covid 19 pandemic on the performance of Moroccan and European public administrations.